Open Innovation for Business-IT Academic Institution: Case of Oman - Matriano, Maria Teresa (Advances in Social Sciences Research Journal, 2019)
Oman’s economic activities are often centered on oil production and export with very limited focus given towards enhancing its private sector. The more traditional approach to business also inhibits the growth of some of the business organizations in the country because of the lack of attention to innovation. However, finding new opportunities through innovation can be also made possible through a mutually beneficial partnership with the academic sector through open innovation. The cooperation between the business IT academic institutions and the business sector is key in achieving success in innovation on an economic level. The shared knowledge between the two sectors is crucial in ensuring that new ideas and technologies are delivered to the end consumers in a form of an innovative product of services. In the case of Oman, several challenges are facing both the academic and the private sector in terms of establishing an open innovation partnership. In this discussion, the concept of open innovation for business IT will be highlighted with emphasis given to the current state of open innovation partnerships in Oman. In addition, the discussion will also explore the advantages of open innovation in business IT in terms of fostering innovation through research and development. Keywords: Open Innovation, Business IT, Institutional Partnership, Research and Development